Transforming Aircraft Purchase Management With AI: Opportunities, Challenges, & Future – A Mini Review - Mohd Ariffin, Siti Zubaidah; Rambeli@Ramli , Norimah; Wan Mustaffa, Wan Salmuni; Mahmood, Ahmad; Abdul Rahman, Rafiduraida; Hanafi, Hafizul Fahri; Abdul Wahi , Hariyaty (Journal of Islamic, Social, Economics and Development, 2025)
This mini review, Transforming Aircraft Purchase Management with AI: Opportunities, Challenges, and Future Directions, aims to critically examine the role of artificial intelligence (AI) in optimizing aircraft purchase management. Given the financial, operational, and strategic significance of fleet acquisition, the review explores AI’s potential to enhance predictive accuracy, risk assessment, supplier evaluation, and decision-making, while also identifying limitations, controversies, and research gaps.